2005
DOI: 10.1007/s00421-005-0096-2
|View full text |Cite
|
Sign up to set email alerts
|

Minor changes in blood lipids after 6 weeks of high-volume low- intensity physical activity with strict energy balance control

Abstract: Physical activity has been shown to favorably affect metabolic risk markers, including blood lipids. The impact of high-energy turnover, without influencing the traditionally used markers of exercise training effects, on blood lipids is still unclear. The aim was to study the effect of high-volume low-intensity physical activity on the blood lipid pattern, with a tight control of diet and energy balance. Eight untrained men [42.5 (12.1) years, body mass index 24.2 (2.8) kg m(-2)] were tested in two different 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…HDL-C level decreased in both groups being statistically significant only in training group. In two studies, after 8-week (Martin et al, 2003) and 6-week (Branth et al, 2006) endurance training performed in similar duration with the present study, HDL-C levels of the participants were reported to significantly increase and LDL-C levels did not change. Discrepancies between previous studies and this study may be due to the differences in frequency, duration and intensity of exercises in training programs performed.…”
Section: Discussionsupporting
confidence: 79%
“…HDL-C level decreased in both groups being statistically significant only in training group. In two studies, after 8-week (Martin et al, 2003) and 6-week (Branth et al, 2006) endurance training performed in similar duration with the present study, HDL-C levels of the participants were reported to significantly increase and LDL-C levels did not change. Discrepancies between previous studies and this study may be due to the differences in frequency, duration and intensity of exercises in training programs performed.…”
Section: Discussionsupporting
confidence: 79%
“…Branth et al . in their studies on a group of middle-aged training men did not observe changes in the lipid profile in those subjects whose energy expenditure connected with the exercise was balanced by an increased energy intake [ 42 ]. In women examined by us, similarly to the men tested by Branth et al ., an increased energy intake was observed during the 12-week training, which could have resulted in a lack of favourable changes in their plasma lipids profile.…”
Section: Discussionmentioning
confidence: 99%
“…LDL-ch level did not change significantly after 2-month experiment in our study (Table 2). Some authors compared LDLch concentration between physically active and passive subjects and did not find any significant differences (27), while the others determined that LDL-ch concentration in blood of physically active subjects was 7-12% lower as compared to subjects who did not exercise (28).…”
Section: Discussionmentioning
confidence: 99%